Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. The use of special education teachers in Makkah Al-Mukarramah for electronic educational games as an educational medium and the obstacles to their useMrs. Waed Juma Rashid Al-Subhi, Co-Prof. Abdullah Musharraf Alshaaeir2. Design E-learning Environment Based on Learning Platforms and its impact on Achievement and Developing Digital Citizenship Skills in the Computer course for Middle school studentsMrs. Manal Rabeh Alhejaili3. The Level of Achieving Intermediate Stage Curricula the National-Transformation Program 2020 Goals from the point of view of teachers in the schools of the West Riyadh Office for BoysMr. Bandar Mohammd Alsomaie , Co-Prof. Ahmed Hasan Albdour4. The Effect of Creating 3D Software Using (CoSpaces Edu) To Develop Coding Skills for Primary School StudentsMrs. Areej Abdullah Alghamdi , Mrs. Layla Hamad Harboush , Co-Prof. Amjaad Tariq Mujallid5. The impact of teaching by the guided imagination strategy on developing creative expression skills for high school students in Republic of YemenDr. Bushra Muhammad Yahya Rafiq Allah6. Designing and testing a module based on the integrated approach between the subjects of geography and natural sciences. A case study of the common core science stream in the Moroccan high schoolProf. Abdelali Soulali7. The Role of Social Upbringing Institutions in Raising Awareness and Counseling about the Danger of Drugs, Khartoum, SudanDr. Shaza Omer AliThe Level of Conceptual Understanding of Functions and their Transformations and its Relationship with the Productive Motivation among Mathematics Students in the Faculty of Education University of Sana`aInstructor \ Abdol-Rahman Ali Saleh Al-Mahab , Prof. Radman Mohamed Saeed
Keywords: Journal of Educational and Psychological Sciences